2017
DOI: 10.1038/s41598-017-09725-w
|View full text |Cite
|
Sign up to set email alerts
|

MAPK1 of Leishmania donovani interacts and phosphorylates HSP70 and HSP90 subunits of foldosome complex

Abstract: MAP kinases (MAPK) are the most downstream kinases in signal transduction cascades and regulate critical cellular activities such as cell proliferation, differentiation, mortality, stress response, and apoptosis. The Leishmania donovani MAPK1 (LdMAPK1) is involved in parasite viability and drug resistance, but its substrates have not been identified yet. Aiming to identify the possible targets(s) of LdMAPK1, we sought to isolate interacting partners by co-immunoprecipitation, gel electrophoresis and mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Such natural modulation pathways may include protein kinases, since it was shown that HSP90 and several associated chaperones and cochaperones are the subjects of amastigote stage-specific protein phosphorylation ( 87 ). The recent finding that HSP90 and HSP70 are both substrates for MAP kinase 1 ( 88 ) supports this idea, since MAP kinase 1 or LmxMPK1 is crucial for the intracellular survival of Leishmania ( 89 ). Another kinase recently shown (A. Hombach-Barrigah, K. Bartsch, D. Smirlis, H. Rosenqvist, A. MacDonald, F. Dingli, D. Loew, G. F. Späth, N. Rachidi, M. Wiese, and J. Clos, unpublished data) to catalyze HSP90 phosphorylation is casein kinase 1.2 ( 90 , 91 ), which is crucial for promastigote growth ( 92 ) and is also found in the HSP90-containing exosome-like vesicles that are shed by Leishmania as a means for host cell immune modulation ( 42 , 93 ).…”
Section: Discussionmentioning
confidence: 92%
“…Such natural modulation pathways may include protein kinases, since it was shown that HSP90 and several associated chaperones and cochaperones are the subjects of amastigote stage-specific protein phosphorylation ( 87 ). The recent finding that HSP90 and HSP70 are both substrates for MAP kinase 1 ( 88 ) supports this idea, since MAP kinase 1 or LmxMPK1 is crucial for the intracellular survival of Leishmania ( 89 ). Another kinase recently shown (A. Hombach-Barrigah, K. Bartsch, D. Smirlis, H. Rosenqvist, A. MacDonald, F. Dingli, D. Loew, G. F. Späth, N. Rachidi, M. Wiese, and J. Clos, unpublished data) to catalyze HSP90 phosphorylation is casein kinase 1.2 ( 90 , 91 ), which is crucial for promastigote growth ( 92 ) and is also found in the HSP90-containing exosome-like vesicles that are shed by Leishmania as a means for host cell immune modulation ( 42 , 93 ).…”
Section: Discussionmentioning
confidence: 92%
“…The escape variants display wild-type level temperature tolerance and in vitro proliferation rates and chemoresistance, due to a massive amplification of the casein kinase 1.2 (CK1.2) gene. We further show that HSP23, but also P23, are substrates of CK1.2, establishing yet another link 44,45 between protein kinase-mediated signalling and the chaperone machinery of Leishmania.…”
mentioning
confidence: 56%
“…HSP90 has been recently shown to act as a downstream client of phosphorylation-mediated cellular signalling in L. donovani [45]. Similarly, HSPs in the HSP90 foldosome complex in L. donovani were recently shown to be phosphorylated by mitogen-activated protein kinase-1 [46]. Beyond their well-established role in protein folding, HSPs and many components of the cellular protein folding machinery are found to be associated with signalling molecules including protein kinases, transcription factors and receptors and mediate their activity [47].…”
Section: Discussionmentioning
confidence: 99%